Empowerment of PUS (Couples of Childbearing Age) in Efforts to Prevent Stunting - Rokayah, Yayah (Jurnal Menara Pengabmas, 2024)
According to Riskesdas, in 2018 the incidence of stunting in Indonesia reached 10.2% with a prevalence of stunting in children under five of 30.8% (Ministry of Health, 2018). The problem of stunting is generally caused by a lack of nutritious food intake, the presence of disease and the mother's low level of knowledge regarding children's nutritional requirements, parents' wrong parenting patterns. 1The prevalence of stunting under five in Lebak district is 6.4%. Preliminary studies at PKM Kalang Anyar in 2022 show that of the total number of children under five, 53 are stunted. Sangiang Tanjung is one of the villages with the highest incidence of stunting, namely 25 people (4.96%). One solution to reduce the incidence of stunting is the need for an effort to empower PUS (Couples of Childbearing Age) in efforts to prevent stunting with the aim of increasing the knowledge and skills of PUS in providing good parenting patterns, through serving nutritious food. The methods used include pre and post tests as well as role play on how to serve food using food models. The target of the activity is EFA as many as 40 people. The results obtained were that the majority of PUS (87.5%) experienced an increase in knowledge with a p value of 0.003 (p < α), and almost all PUS (90.0%) experienced a change in skills towards the better (increased), a p value of 0.001 (p < α). To further increase EFA knowledge about stunting prevention, it is necessary to provide continuous information in posyandu activities.